2002
DOI: 10.1007/s00127-002-0575-2
|View full text |Cite
|
Sign up to set email alerts
|

A French study of the Dominic Interactive

Abstract: The instrument performed well in the French context. The potential advantages of using the Dominic Interactive (children enjoy the activity, parents approve of it, it is relatively cost-effective, etc.) suggest its applicability in other settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 2 publications
0
42
0
7
Order By: Relevance
“…In this study, 250 typical children and 150 inpatient and outpatient clinic children were assessed with the DI. The two groups were significantly different on most DI scales, with the treatment-based group reaching the clinical ranges more frequently compared to typical children (Valla et al, 2002). Thus, although preliminary evidence supports the discriminant validity of this scale, further research is needed about the scale's reliability and validity.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…In this study, 250 typical children and 150 inpatient and outpatient clinic children were assessed with the DI. The two groups were significantly different on most DI scales, with the treatment-based group reaching the clinical ranges more frequently compared to typical children (Valla et al, 2002). Thus, although preliminary evidence supports the discriminant validity of this scale, further research is needed about the scale's reliability and validity.…”
mentioning
confidence: 83%
“…A recent study using the DI in young French children reported significant differences between a school-based population and an outpatient clinical sample in terms of the proportion of children reaching two cutoff points designed to estimate clinical severity based on the number of symptoms the child endorses for a given disorder (Valla et al, 2002). In this study, 250 typical children and 150 inpatient and outpatient clinic children were assessed with the DI.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…De nombreuses études ont jugé de la solidité des propriétés psychométriques du Dominique Interactif pour Adolescents (Hardoon et Derevnesky, 2002 ;Smolla,Valla, Bergeron, Berthiaume et St-Georges, 2004 ;Valla et al, 2002). Une étude réalisée auprès de 607 adolescents de la région de Montréal âgés de 12 à 15 ans, démontre que pour la majorité des échelles, la consistance interne varie de ,69 à ,89, alors que la fidélité test-retest = de ,78 à ,87 (Bergeron et al, 2010).…”
Section: Instrumentsunclassified
“…A final total sample of 607 French-speaking adolescents living in the Montreal urban area was culled: 465 adolescents from the community and 142 from psychiatric outpatient clinics. As no psychometric differences were observed between the English and French versions of the DI in children aged 6 to 11 years, 23,44,45 only French-speaking adolescents were recruited for our study. The community sample was balanced according to age, sex, and the socioeconomic status of the school the adolescent was attending.…”
Section: Participantsmentioning
confidence: 99%